Pelaksanaan Perjanjian Hutang Piutang Non Kontraktual Dengan Jaminan Kebendaan(Studi Perlindungan Hukum Bagi Para Pihak di Madiun) - Rahim Khasana, Frisca, Darsono, SH,MH (2016)
Testament accounts payable held in Madiun community to be non contractual or verbal. Non-contractual agreements accounts payable trust are the words spoken by the parties. Accounts payable non contractual agreements implemented based on an agreement and trust between the parties. Implementation agreements verbal accounts payable carried out only with the words of the party only. Problems arose one of them defaults and settlement of these problems is done by way of negotiations both parties entered into an agreement . Forms of legal protection for the parties to the non-contractual accounts payable namely the shape of repressive and preventive legal protection. Supposedly in the implementation of noncontractual agreements accounts payable melibatakan government or better if you use the official financial institutions .